Observations of community-based multidisciplinary team meetings in health and social care for older people with long term conditions in England - Nick Douglas; Nicholas Mays; Mustafa Al-Haboubi; Tommaso Manacorda; Lavanya Thana; Gerald Wistow; Mary Alison Durand (BMC, 2022)
Abstract Background Community-based multi-disciplinary teams (MDTs) are the most common means to encourage health and social care service integration in England yet are rarely studied or directly observed. This paper reports on two rounds of non-participant observations of community-based multi-disciplinary team (MDT) meetings in two localities, as part of an evaluation of the Integrated Care and Support Pioneers Programme. We sought to understand how MDT meetings coordinate care and identify their 'added value' over bilateral discussions. Methods Two rounds of structured non-participant observations of 11 MDTs (28 meetings) in an inner city and mixed urban-rural area in England (June 2019-February 2020), using a group analysis approach. Results Despite diverse settings, attendance and caseloads, MDTs adopted similar processes of case management: presentation; information seeking/sharing; narrative construction; solution seeking; decision-making and task allocation. Patient-centredness was evident but scope to strengthen 'patient-voice' exists. MDTs were hampered by information governance rules and lack of interoperability between patient databases. Meetings were characterised by mutual respect and collegiality with little challenge. Decision-making appeared non-hierarchical, often involving dyads or triads of professionals. 'Added value' lay in: rapid patient information sharing; better understanding of contributing agencies' services; planning strategies for patients that providers had struggled to find the right way to engage satisfactorily; and managing risk and providing mutual support in stressful cases. Conclusions More attention needs to be given to removing barriers to information sharing, creating scope for constructive challenge between staff and deciding when to remove cases from the caseload.